2013
DOI: 10.1108/rpj-12-2011-0127
|View full text |Cite
|
Sign up to set email alerts
|

Additive manufacturing (AM) and nanotechnology: promises and challenges

Abstract: PurposeThis paper aims to provide a review of available published literature in which nanostructures are incorporated into AM printing media as an attempt to improve the properties of the final printed part. The purpose of this article is to summarize the research done to date, to highlight successes in the field, and to identify opportunities that the union of AM and nanotechnology could bring to science and technology.Design/methodology/approachResearch in which metal, ceramic, and carbon nanomaterials have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
231
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 412 publications
(235 citation statements)
references
References 72 publications
0
231
0
4
Order By: Relevance
“…Incorporating (nano)materials to AM is realized via two ways; either use of AM for host matrix material with intermittent stoppages of the batch print job and introduction of nanomaterials automatically or manually, or pre-mixing of the nanomaterials into the host matrix, followed by AM of the nanocomposite mixture as a complete part. This will lead to enhancement of mechanical properties, increase of thermal and electrical conductivity, lower sintering temperatures, and will affect dimensional accuracy, as the incorporation of carbonaceous and metallic nanoparticles has been found to decrease deflection and shrinkage in various AM processes, due to more effective heat dissipation and lower temperature processing [19]. However, AM methods have their own limitations when nanoparticles are introduced, depending on the principle of operation, such as nozzle clogging for FFF, aggregation within liquid media and viscosity increase for ink-jet and stereolithography, nano-powder aggregation and decreased flowability in SLS processes, as well as rough surface finish of printed parts, etc.…”
Section: D Nanofabrication-printing Of Nanomaterialsmentioning
confidence: 99%
“…Incorporating (nano)materials to AM is realized via two ways; either use of AM for host matrix material with intermittent stoppages of the batch print job and introduction of nanomaterials automatically or manually, or pre-mixing of the nanomaterials into the host matrix, followed by AM of the nanocomposite mixture as a complete part. This will lead to enhancement of mechanical properties, increase of thermal and electrical conductivity, lower sintering temperatures, and will affect dimensional accuracy, as the incorporation of carbonaceous and metallic nanoparticles has been found to decrease deflection and shrinkage in various AM processes, due to more effective heat dissipation and lower temperature processing [19]. However, AM methods have their own limitations when nanoparticles are introduced, depending on the principle of operation, such as nozzle clogging for FFF, aggregation within liquid media and viscosity increase for ink-jet and stereolithography, nano-powder aggregation and decreased flowability in SLS processes, as well as rough surface finish of printed parts, etc.…”
Section: D Nanofabrication-printing Of Nanomaterialsmentioning
confidence: 99%
“…It is concluded that mechanical properties, thermal and electric conductivity, sintering temperatures, dimensional accuracy of nanocomposites through AM technology can be improved, but there are still a number of barriers in each AM method such as; aggregation within printing media, the rough surface finish of printed parts and nozzle clogging. By other meaning, standardise process parameters and synthesis methods for different nanomaterials and processes don't exist by sufficient way till now [54]. One of nanocomposite components through AM technology was the manufacturing of TiC/Ti nanocomposite parts using SLS.…”
Section: Nano-compositesmentioning
confidence: 99%
“…In some cases, tight tolerances need to be met for an AMproduced item to be used as a replacement part (Lively, 2014). Even then, material properties such as strength, electrical and thermal conductivity, and optical transparency typically have inferior properties due to the anisotropy caused by the layer by layer approach (Ivanova, Williams, & Campbell, 2013). This directional weakness means that the parts cannot be stressed in the same way that a molded or welded part can.…”
mentioning
confidence: 99%